AIDS, Intimacy and Care in Rural KwaZulu-Natal A Kinship of Bones - Henderson, Patricia C. (Care & Welfare, 2011)
In 2003-2006, Patricia Henderson lived in the South African province of KwaZulu-Natal where she recorded the experiences of people living with HIV/AIDS. In this illuminating study, she recounts the concerns of rural people and explores local repertoires through which illness was folded into everyday life. The book spans a period when antiretroviral medication was not available, and moves on to a time when the treatment became accessible. Hope gradually became manifest in the recovery of a number of people through antiretroviral therapies and 'the return' of bodies they could recognise as their own. This research implies that protracted interaction with people over time, offers insights into the unfolding textures of everyday life, in particular in its focus on suffering, social and structural inequality, illness, violence, mourning, sensibility, care and intimacy.